PROSPECTS OF USING MODERN INNOVATIVE TECHNOLOGIES IN EDUCATION - Oybek Holbutayevich Omonbayev (International Journal of Literature and Language Studies, 2026)
Abstract. This article examines the advantages, methodological bases and possibilities of using modern innovative and pedagogical technologies in the educational process.